Diverse microbiome functions, limited temporal variation and substantial genomic conservation within sedimentary and granite rock deep underground research laboratories - Yuki Amano; Rohan Sachdeva; Daniel Gittins; Karthik Anantharaman; Shufei Lei; Luis E. Valentin-Alvarado; Spencer Diamond; Hikari Beppu; Teruki Iwatsuki; Akihito Mochizuki; Kazuya Miyakawa; Eiichi Ishii; et al. (Environmental Microbiome)
Abstract Background Underground research laboratories (URLs) provide a window on the deep biosphere and enable investigation of potential microbial impacts on nuclear waste, CO2 and H2 stored in the subsurface. We carried out the first multi-year study of groundwater microbiomes sampled from defined intervals between 140 and 400 m below the surface of the Horonobe and Mizunami URLs, Japan. Results We reconstructed draft genomes for > 90% of all organisms detected over a four year period. The Horonobe and Mizunami microbiomes are dissimilar, likely because the Mizunami URL is hosted in granitic rock and the Horonobe URL in sedimentary rock. Despite this, hydrogen metabolism, rubisco-based CO2 fixation, reduction of nitrogen compounds and sulfate reduction are well represented functions in microbiomes from both URLs, although methane metabolism is more prevalent at the organic- and CO2-rich Horonobe URL. High fluid flow zones and proximity to subsurface tunnels select for candidate phyla radiation bacteria in the Mizunami URL. We detected near-identical genotypes for approximately one third of all genomically defined organisms at multiple depths within the Horonobe URL. This cannot be explained by inactivity, as in situ growth was detected for some bacteria, albeit at slow rates. Given the current low hydraulic conductivity and groundwater compositional heterogeneity, ongoing inter-site strain dispersal seems unlikely. Alternatively, the Horonobe URL microbiome homogeneity may be explained by higher groundwater mobility during the last glacial period. Genotypically-defined species closely related to those detected in the URLs were identified in three other subsurface environments in the USA. Thus, dispersal rates between widely separated underground sites may be fast enough relative to mutation rates to have precluded substantial divergence in species composition. Species overlaps between subsurface locations on different continents constrain expectations regarding the scale of global subsurface biodiversity. Conclusions Our analyses reveal microbiome stability in the sedimentary rocks and surprising microbial community compositional and genotypic overlap over sites separated by hundreds of meters of rock, potentially explained by dispersal via slow groundwater flow or during a prior hydrological regime. Overall, microbiome and geochemical stability over the study period has important implications for underground storage applications.